2019
DOI: 10.1186/s13068-019-1406-y
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of bamboo lignocellulose by bamboo snout beetle Cyrtotrachelus buqueti in vivo and vitro: efficiency and mechanism

Abstract: Background As an important biomass raw material, the lignocellulose in bamboo is of significant value in energy conversion. The conversion of bamboo lignocellulose into fermentable reducing sugar, i.e. the degradation of bamboo lignocellulose, is an important step in lignocellulose conversion. However, little research has focussed on excavating the enzymes and microbes that are related to the degradation of bamboo lignocellulose, which is important for its utilisation. This study used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…As products of photosynthesis, carbohydrates are the main source of stored energy for host plants and insect herbivores. In our previous study, we found that C. buqueti had a large scale of carbohydrate-active enzyme genes and very high degradation efficiency for the lignocellulose of B. emeiensis, and the lignocellulose of B. emeiensis was mainly composed of lignin, cellulose and hemicellulose, the three components of which were mainly sugars and their derivatives [17,18]. This study further explored the role of starch and sucrose metabolism related to carbohydrate in B. emeiensis based on transcriptome and metabolome association analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As products of photosynthesis, carbohydrates are the main source of stored energy for host plants and insect herbivores. In our previous study, we found that C. buqueti had a large scale of carbohydrate-active enzyme genes and very high degradation efficiency for the lignocellulose of B. emeiensis, and the lignocellulose of B. emeiensis was mainly composed of lignin, cellulose and hemicellulose, the three components of which were mainly sugars and their derivatives [17,18]. This study further explored the role of starch and sucrose metabolism related to carbohydrate in B. emeiensis based on transcriptome and metabolome association analysis.…”
Section: Discussionmentioning
confidence: 99%
“…pabularia) had a common mechanism of induction of changes in metabolites under methyl jasmonate induction and Cabbage Looper (Trichoplusia ni Hübner) feeding stress, implying that it is useful for pest control and nutritional quality of kale [15] B. emeiensis is widely distributed in Southwest China and is a plant with high economic value that is currently used in papermaking, landscaping and environmental protection [16]. In our previous study, we identified a large number of carbohydrate genes in C. buqueti [17], analyzed the ability of C. buqueti to degrade B. emeiensis lignocellulose, and explored the potential of using B. emeiensis for bioenergy conversion [18]. In the process, we learned that C. buqueti is a B. emeiensis specialist insect that severely damages and inhibits the development of bamboo shoots and affects the bamboo success rate of B. emeiensis.…”
Section: Introductionmentioning
confidence: 99%
“…This neglect is mostly due to the fact that relative to insects, microorganisms are easier to get access to and to cultivate in the laboratory. With more than 130 000 species, each of whose respective genomes harbor on average more than 10 genes encoding various PCWDEs, Phytophaga beetles represent the largest, under‐investigated pool of novel enzymes with potential use in the generation of biofuels …”
Section: Discussionmentioning
confidence: 99%
“…The bamboo materials were sampled from the bamboo botanical garden of the Bamboo Diseases and Pests Control and Resources Development Key Laboratory of Sichuan Province, China. The bamboo powders were prepared as described by Luo et al [67]. BP samples were treated with 3% (w/w) Tween-80 to enhance alkali pretreatment efficiency.…”
Section: Pretreament Of the Raw Bamboo Materialsmentioning
confidence: 99%